(untitled) (Confluências | Revista Interdisciplinar de Sociologia e Direito, 2019)
The productive arrangement of intimate fashion in the Nova Friburgo region (Rio de Janeiro, Brazil) was identified by political institutions in the late 1990s and became the target of promotional initiatives. With this, a considerable number and variety of institutions began to develop actions for the territory. The purpose of this article is to investigate the perceptions of local actors, through field interviews, about these political experiences. From the theoretical framework of the Local Innovative and Productive System (LIPS), a mosaic of narratives based on the perspectives of the local actors was constructed. The confrontation between these narratives and the political discourse supported by extralocal institutions reveals important conclusions related to the LIPS development policies that will be presented in this article.